Do you prefer to collaborate with students pursuing the same goals?: A network analysis of physical education classes - Schüßler, Annabell; Holler, Cornelius; Hill, Yannick (British journal of educational psychology, 2025)
Background At school, students need to learn to collaborate with others to achieve common objectives. However, we are lacking insights into how students determine preferred collaboration partners, while multiple plausible factors, such as similar goal orientations, can be derived from the literature. Aims We examined whether students prefer teammates in physical education based on similar achievement goals, stronger degrees of goal orientation, the same gender, and friendship. Sample We recruited 364 students aged 10-16, across 16 classrooms in three German secondary schools. Methods Social Network Analyses with Exponential Random Graph Models (ERGMs) are applied to identify relevant achievement-goal dimensions for teammate selection and to assess preferences for collaborating with peers with similar or stronger degrees of goal orientation or with their friends. Results Our findings indicate that students prefer to collaborate with peers who display similar levels of achievement-goal orientations in physical education. Additionally, students prefer collaborating with friends and often select peers of the same gender, with boys being chosen more frequently than girls. When students do not pick their friends, they seek out peers with stronger degrees of goal orientation, specifically for goals aimed at winning. Conclusion When collaborating in sports games, peers are faced with the dilemma of choosing between friends and the desire to win. Teachers should supervise the formation of groups and, depending on the aim of a particular lesson, should allocate students on the basis of different characteristics or let students choose their own group members.
Zuerst veröffentlicht: 06 March 2025
Gesehen am 23.02.2026